2022
DOI: 10.1002/cctc.202200841
|View full text |Cite
|
Sign up to set email alerts
|

The Puzzling Question about the Origin of the Second Electron in the Molecular Photocatalytic Reduction of CO2

Abstract: Herein, a new supramolecular photocatalyst RuRe3 containing three Re(dmb)CO 3 Cl (dmb = 4,4'-dimethyl-2,2'-bipyridine) (Re) building blocks connected through an ethylene bridge to one [Ru(dmb) 3 ] 2 + -unit (Ru) is presented. We investigated the photophysical properties of this novel tetranuclear complex and compared these to compounds with one (RuRe) and two (RuRe2) catalytic units. Under irradiation, all three photocatalysts exhibit high activity and photostability for the reduction of CO 2 to CO, with RuRe3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…[27][28][29] Several bimetallic Ru(II)-Re(I) polypyridyl complexes, where the metal ions are connected through various bridging ligands, have been reported and demonstrated to have potential applications as efficient photocatalysts for CO 2 fixation. [30][31][32] By comparison, bimetallic compounds that contain a Re(I) unit and other metal ions such as Pt(II) and Pd(II) have not been investigated extensively, and only a few examples are known in the literature. 33,34 In a previous study, we reported the ligand L1 (Chart 1) that has two different binding units, i.e., 2-(2 0 -pyridyl)benzimidazolyl (py-im) and 2-(2 0 -pyridyl)indolyl (py-in) moieties, linked together by a benzene ring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Several bimetallic Ru(II)-Re(I) polypyridyl complexes, where the metal ions are connected through various bridging ligands, have been reported and demonstrated to have potential applications as efficient photocatalysts for CO 2 fixation. [30][31][32] By comparison, bimetallic compounds that contain a Re(I) unit and other metal ions such as Pt(II) and Pd(II) have not been investigated extensively, and only a few examples are known in the literature. 33,34 In a previous study, we reported the ligand L1 (Chart 1) that has two different binding units, i.e., 2-(2 0 -pyridyl)benzimidazolyl (py-im) and 2-(2 0 -pyridyl)indolyl (py-in) moieties, linked together by a benzene ring.…”
Section: Introductionmentioning
confidence: 99%
“…27–29 Several bimetallic Ru( ii )–Re( i ) polypyridyl complexes, where the metal ions are connected through various bridging ligands, have been reported and demonstrated to have potential applications as efficient photocatalysts for CO 2 fixation. 30–32 By comparison, bimetallic compounds that contain a Re( i ) unit and other metal ions such as Pt( ii ) and Pd( ii ) have not been investigated extensively, and only a few examples are known in the literature. 33,34…”
Section: Introductionmentioning
confidence: 99%